1994
DOI: 10.1111/j.1365-2672.1994.tb03084.x
|View full text |Cite
|
Sign up to set email alerts
|

Amylase production by a Gram‐positive bacterium isolated from fermenting tef (Eragrostis tef)

Abstract: Bacillus sp. A‐001, which produced large amounts of amylase, was isolated from fermenting tef (Eragrostis tef) on tryptone soya agar supplemented with 1% starch. The organism grew between pH 4.5 and 10.5 with an optimum at 7–7.5. Growth occurred between 20 and 55°C but the optimum was about 35–40°C. At optimum medium pH (7.5) and a temperature of 35°C the organism entered the stationary phase after about 72 h and amylase production was at its highest (9.6 units ml‐1) at this time. Enzyme activity was optimal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 11 publications
1
24
0
12
Order By: Relevance
“…Para considerar um microrganismo como um bom produtor de enzimas extracelulares em meio sólido, LEALEM e GASHE 18 A habilidade de rizóbios em degradar amido tem sido discutida em alguns trabalhos. Estudos como os de BERTHELOT e DELMOTTE 5 , SINGH e SINGH 30 e VAN SPRONSEN et al 37 sugerem uma possível participação de algumas glicosidases, como as amilases, no estabelecimento intracelular da simbiose leguminosa versus rizóbia.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Para considerar um microrganismo como um bom produtor de enzimas extracelulares em meio sólido, LEALEM e GASHE 18 A habilidade de rizóbios em degradar amido tem sido discutida em alguns trabalhos. Estudos como os de BERTHELOT e DELMOTTE 5 , SINGH e SINGH 30 e VAN SPRONSEN et al 37 sugerem uma possível participação de algumas glicosidases, como as amilases, no estabelecimento intracelular da simbiose leguminosa versus rizóbia.…”
Section: Resultsunclassified
“…Neste trabalho, o registro de uma forte correlação entre "IE" e "DMH" (r = 0,86; p < 0,01) confirma relatos anteriores 18,32 . Contudo, vale mencionar que, apesar da estreita relação entre as variáveis "DMH" e "IE", elas não estão significativamente relacionadas com o diâmetro médio da colônia (DMC) (Tabela 3).…”
Section: Resultsunclassified
“…Lealem e Gashe (1994) [15] estabelecem que para que um micro-organismo seja considerado como um bom produtor de enzimas extracelulares em meio sólido, é necessário que o seu IE seja maior ou igual a 2,0. Dessa forma, foi possível classificar os micro-organismos ANAG01, ANCA01, ANRAS01 e ANRAS02 como bons produtores de amilase microbiana, sendo o ANRAS01 o melhor entre eles, visto seu maior valor de IE (Tabela 3).…”
Section: : Médias De Três Repetições Médias Seguidas Pela Mesma Letunclassified
“…Além disso, o único fungo considerado como viável para produção da enzima em questão é o isolado PDARAS02, uma vez que os demais apresentaram valores de IE abaixo de 2,0 [15].…”
Section: : Médias De Três Repetições Médias Seguidas Pela Mesma Letunclassified
“…Fungaro and Maccheroni (2002) suggested that EI greater than 1.0 are a reliable indicator for the presence of enzymes excreted by microorganisms, while EI ≥ 2.0 is considered good indicator for potential enzyme production by a bacterium (Lealem and Gashe, 1994). However, while for lipase the variation in EI is minimal (~2.0), for cellulase and lipase the scale of EI values vary between >2.0 to >6.0.…”
Section: Amylase Activitymentioning
confidence: 99%